Antioxidant liver protection of Vitis vinifera L. (grape) skin and seed - Sandoval, Miguel (2008)
Objective: To determine by TBARS test (substances reactive to thiobarbituric acid) the antioxidant and liver protection effect induced by Vitts vinifera L. grape skin and seeds in animals of experimentation with alcoholic aggression. Design: Experimental study. Setting: Alberto Guzman Barron Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Albino male adult mice and Vitis vinifera L. (grape) skin and seeds. Methods: Grape skin and seeds were brought from Cañete Valley; they were separated manually, squeezed in gauze and dissecated with flowing air at 40º C for 24 hours; then they were grinded and the skin and seeds mixture (skin-seeds) were administered ad libitum in the diet. We used 104 albino male adult mice, separated in groups, that received: (A) skin-seeds at 20%; (B) alcohol at 5%; (C) skin-seeds with alcohol; (D) silimarina 50 mg/100 g of food; (E) silimarina with alcohol; and, (F) control group. Under ether anesthesia and by laparotomy, liver was removed, weighted and analyzed for lipoperoxidation by TBARS, and hepatomegaly was determined by weight at 24, 48 and 72 hours, and at 4, 5 and 7 days of treatment. Main outcome measures: Liver lipoperoxidation and hepatomegaly. Results: Hepatomegaly was observed at 24 hours (36,68% liver mass increment) in the alcohol group and was less in the skins-seeds group. TBARS test was higher in the alcohol group (63,91 to 67,07 nmol/g-tissue) and was less in the skin-seeds group (40,85 to 47,46 nmol/g-tissue); in the skin-seeds with alcohol group it was 43 to 63 nmol/g-tissue and protection was seen up to the fifth day (44 nmol/g-tissue). Conclusions: Skin-seeds administered orally in the diet at 20% of weight protected liver tissue up to the fifth day of constant injury with 5% alcohol.